Cloth Clues : Exploring Forensic Secrets Through Maharashtra’s Rich Fabric Heritage (International Journal of Scientific Research in Science and Technology, 2024)
The present study explores the textile heritage of Maharashtra, with particular attention on the differences in textile use throughout the state’s five main regions: Konkan, Vidarbha, Marathwada, Khandesh, and North Maharashtra. Through the use of surveys, in-person interviews, and data analysis, it investigates how environmental conditions, cultural traditions, and societal norms impact fabric choices in each place. The study underscores the cultural importance of traditional attire in Maharashtra and emphasizes how it promotes community cohesion, historical celebration, and cultural identity preservation. The elaborate Vidarbha kurtas and the colourful Konkan sarees, Maharashtra’s traditional clothing reflects the region’s cultural geography. The main goal of the study is to examine how environmental factors influence fabric preferences in each of the state’s regions. For example, the Konkan’s humid coastal climate is ideal for lightweight textiles like silk and cotton, but Vidarbha and North Maharashtra’s colder climates demand the usage of warmer materials like wollen cloths.Further investigation into regional variations in fabric use entails a look at weaving methods, style trends, and cultural practices. Every area is proud of its unique textile heritage, which displays the artistic customs and skill of its people. Examples are the elaborate Kasuti needlework of Konkan and the silk Paithani sarees of Marathwada.The results of this study will also have a big impact on Maharashtra’s methods for investigating crimes and analyzing evidence. Law enforcement officials can more effectively connect evidence to particular places, towns, or people by knowing the fabric selections and cultural customs that are particular to each area. For example, discovering a unique weaving technique or old object at a crime scene can provide important details about the criminal’s upbringing or place of origin. Moreover, knowing how fabrics are used differently across different regions can help identify the origins of materials used in illicit operations like counterfeiting and smuggling to sum up, this research offers insightful information on Maharashtra’s textile history and how it relates to crime analysis and investigation. This improves law enforcement’s capacity and fosters a greater awareness of the state’s cultural variety.